2015
DOI: 10.1038/srep12018
|View full text |Cite
|
Sign up to set email alerts
|

A novel crosstalk between TLR4- and NOD2-mediated signaling in the regulation of intestinal inflammation

Abstract: Although Toll-like receptor 4 (TLR4)- and nucleotide-binding oligomerization domain 2 (NOD2)-mediated signaling mechanisms have been extensively studied individually, the crosstalk between them in the regulation of intestinal mucosal defense and tissue homeostasis has been underappreciated. Here, we uncover some novel activities of NOD2 by gene expression profiling revealing the global nature of the cross-regulation between TLR4- and NOD2-mediated signaling. Specifically, NOD2 is able to sense the intensity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 55 publications
4
27
0
Order By: Relevance
“…They play a central role in detection of invading pathogens and induction of innate antibacterial and inflammatory responses by recognizing PAMPs. [8][9][10] The intestine expresses multiple TLRs and NODs. [12][13][14][15] Current research has demonstrated that activation of TLR and NOD signaling is associated with multi-layered inflammatory intestinal diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They play a central role in detection of invading pathogens and induction of innate antibacterial and inflammatory responses by recognizing PAMPs. [8][9][10] The intestine expresses multiple TLRs and NODs. [12][13][14][15] Current research has demonstrated that activation of TLR and NOD signaling is associated with multi-layered inflammatory intestinal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] TLRs and NODs are important protein families of inflammatory signaling pathways. [8][9][10] TLRs and NODs are expressed in many tissues including the intestine, [11][12][13][14][15] and play key roles in induction of innate antibacterial and inflammatory responses by recognition of PAMPs. 8,9,16 Interactions of TLRs or NODs with their specific PAMPs trigger downstream signaling events that lead to activation of NF-kB and pathways involving MAPKs, which further provoke the expression of genes encoding pro-inflammatory cytokines, including IL-1b, IL-6 and TNF-a.…”
Section: Introductionmentioning
confidence: 99%
“…Similar data was observed during the infection with L. monocytogenes [9], Mycobacterium avium [54], and also in human DCs stimulated with MDP and TLRs agonists [17]. Furthermore, a very elegant study showed that NOD2 senses the intensity of the TLR4 signaling, resulting in a synergic production of IL12 when the TLR4 signal has low intensity, or inhibition of IL-12 secretion when this signaling is intensified [55]. On the other hand, the expression of IL-12/23p40 was increased in the knockout animals compared to WT, and, as the Il23p19 mRNA levels was maintained, an augment of IL-23 production by infected Nod2 indirectly [13].…”
Section: Nod2supporting
confidence: 70%
“…At the level of genomics, a meta-analysis suggested that the GSTT1 null mutation was significantly associated with susceptibility to IBD [64]. Unaffected ileal samples obtained from carriers of the NOD2 CD-risk allele displayed increased gene expression of DRD4 [65], whereas Nod2 double knockout mouse macrophages displayed a higher Ms4a3 expression relative to wildtype after lipopolysaccharide treatment [66]. Transcription-wise, G0S2 gene expression in mucosal biopsies was found to be predictive of clinical response to infliximab [67].…”
Section: Discussionmentioning
confidence: 99%